(untitled) (Higher Education Politics and Economics, 2022)
By 2025, 70% of Iowa’s jobs will require education or training beyond high school. Despite significant attention and commitment of taxpayers’ dollars, the latest reports suggest these efforts will result in a significant shortcoming. Post-secondary attainment in Iowa has a disparate impact on non-white students, a disparity that has been compounded by COVID-19. This gap between employer needs and workforce talent could put Iowa at a disadvantage to compete in a new global knowledge economy.